2021
DOI: 10.3390/antiox10101577
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein-Rich Leaf Extract as a Broad Inhibitor of Tumour and Macrophage iNOS in an Apc Mutant Rat Model

Abstract: Oleuropein, the major compound found in olive leaves, has been reported to exert numerous pharmacological properties, including anti-inflammatory, anti-diabetic and anti-cancer effects. The purpose of this study was to evaluate, for the first time, the effect of oleuropein-rich leaf extracts (ORLE) in already-developed colon tumours arising in Apc (adenomatous polyposis coli) mutated PIRC rats (F344/NTac-Apcam1137). Here, we were able to investigate in parallel the anti-cancer effect of ORLE, both in vivo and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…However, it is worth mentioning that while OLE-reduced inflammation could result from its direct suppression of the NF-κB pathway, which subsequently inhibits the activation of NLRP3 inflammasomes and RAGE/HMGB1 pathways, the effect could also be indirectly mediated by the reduction of Aβ brain levels. Additional studies would be necessary for confirmation; however, several in vitro studies demonstrated that oleuropein has a direct modulatory effect on inflammation, , suggesting that oleuropein reduces neuroinflammation via both suppressing the NF-κB pathway and Aβ reduction.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth mentioning that while OLE-reduced inflammation could result from its direct suppression of the NF-κB pathway, which subsequently inhibits the activation of NLRP3 inflammasomes and RAGE/HMGB1 pathways, the effect could also be indirectly mediated by the reduction of Aβ brain levels. Additional studies would be necessary for confirmation; however, several in vitro studies demonstrated that oleuropein has a direct modulatory effect on inflammation, , suggesting that oleuropein reduces neuroinflammation via both suppressing the NF-κB pathway and Aβ reduction.…”
Section: Resultsmentioning
confidence: 99%
“…An extensive review of the effects of EVOO and its minor components in preclinical models of colon cancer is also available [ 331 ]. Oleuropein-rich EVOO stimulated in vivo apoptosis of colon cancer cells and peritoneal macrophages in an animal model [ 332 ], and a much more potent nanoencapsulated microemulsion of oleuropein was recently developed and tested in an animal model [ 333 ]. While the addition of oleic acid induced DNA synthesis and growth of the human colorectal adenocarcinoma cell line Caco-2, the subsequent addition of EVOO’s minor components prevented this effect, even inducing apoptosis in the case of hydroxytyrosol and maslinic acid [ 330 ].…”
Section: Resultsmentioning
confidence: 99%
“…Viability of the cells was determined by trypan blue exclusion test. Cultures were periodically monitored for Mycoplasma contamination using Chen’s fluorochrome test, as described in a previous study of ours [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Results were normalized to protein concentration. For RAW264.7 cells, nitrite production was expressed with reference to lipopolysaccharide (LPS; Sigma) as 100% [ 33 ].…”
Section: Methodsmentioning
confidence: 99%